GAMBARAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI DISIPLIN KERJA KARYAWAN SALES FORCE CV. PERKASA TELKOMSELINDO SALATIGA - Fauzia, Farikha Astri; Dongoran, Johnson; Sundari, Ocky (2020)
This type of research is qualitative descriptive with the aim to see the picture and the factors affect the work discipline in CV. Perkasa Telkomselindo Salatiga. The sampling method used in this study is saturation sampling. The subject in this study was all sales force employees of CV. Perkasa Telkomselindo Salatiga which amounted to nine people. Data is obtained directly through in-depth interviews, field records as well as data analyzed using frequency distribution. From the results of data analysis, can be concluded that the view of sales force CV. Perkasa Telkomselindo Salatiga about the work discipline is the attitude of work in a timely manner. The importance of working discipline according to sales force employees is the working discipline is important to make professional employees, in addition to applying the work discipline of sales force employees by working on time and providing excellent service to Costumer. The barriers to the implementation of such work discipline are overtime when the working time has been completed, efforts made to overcome these obstacles by recruiting new employees to increase the number of employees. Related to the factors that are very relevant to the work discipline there are six factors namely the use of uniforms, placement of positions, skills, responsibilities, working time and level of attendance. Factors affecting working discipline are three factors, namely regulation, punishment, and working time utilization. The most significant factors affect the working discipline of the employee's behavior while working. There are two other factors that affect the work discipline of sales force CV. Perkasa Telkomselindo Salatiga, namely environmental factors caused by a poor relationship to the co-worker and a large factor of salary given that caused Overtime.